Цитологічна характеристика селекційних форм Morus alba L. в Донецькому ботанічному саду НАН України - Мітіна, Л.В.; Костирко, Д.Р. (Промышленная ботаника, 2003)
Cytologic studies of the introduced Morus alba L. plants showed th t the selection forms growing on the collection plot of the Donetsk Botanical gardens Nat. Ukr. Acad. Sci of Ukraine are tetraploids obtained by way of experiment. Chromosome set in their somatic cells was 2n=56. For the first time we employed material of forcing treatment for calculation of the number of chromosomes on the apical meristem. It was found that during the stage of diakinesis homologous chromosomes of diploids are combined into bivalents, and in tetraploids tetravalents were formed together with bivalents. The difference between the mean total length of a genome as well as the length of a genome of conventionally average chromosome of bi- and tetraploids is not valid.